Performance properties of hybrid aluminium–composite columnar tube under axial crush force - Paruka, Perowansa; Mat Yasin, Md Hafizil; Mamat, Rizalman; Maleque, Md. Abdul; Md Shah, Md Kamal (Trans Tech Publications, Switzerland, 2015)
This paper presents an experimental work on the influence of number of layers in the overwrap hybrid composite columnars under repeated axial crush force. The columnar test specimens were fabricated by hand lay–up process using commercial available of 0/90° ply oriented epoxy-glass fiber mats. In determining the energy absorption capacity, three different columnar tubes were prepared using one-layer, two-layers and three-layers in order to determine the utilize of such fibers in structural automotive applications. Quasi-static crush test for these tubes was carried out using Instron machine with axial loading. Results showed that the axial crush force and the numbers of layers influenced the level of energy absorption before structures collapse. It is found that the initial peak crush force, mean crush force, crush force efficiency and energy absorption properties of the collapsed hybrid composite columnars were increased by adding of layers in the overwrap thickness.